MOLECULAR-GENETIC «PORTRAIT» OF BREAST CANCER - S. A. Laptiev; M. A. Korzhenevskaia; E. N. Imyanitov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2017)
Understanding genetic mechanisms and detection of biological markers of tumor growth forms an individual molecular phenotype oftransformed cells that characterizes stage of tumor, the ability to metastasize, hormonal sensitivity, chemotherapyefficiencyetc. Mutations in proto- and anti-oncogenes controlling mitotic activity of cells and their ability to DNA reparation are often found in tumor cells in patients with cancer. Defects of classical tumor suppressor genes (BRCA1/2, CHEK2, ATM, PALB2, NBS1, TP53, etc.) determine the hereditary predisposition to breast cancer caused by genomic instability and appearance of «chimeric» genes, aneuploidies and chromosomal aberrations. Breast cancer is a genetically heterogeneous disease with various molecular, biological and clinical features. Identificationof the molecular phenotype of breast carcinomas is an important prognostic factor of the disease, and it helps to individualize the therapeutic approach for patients.